Direct synthesis of acyl fluorides from carboxylic acids using benzothiazolium reagents - Maas, Lilian M.; Haswell, Alex; Hughes, Rory; Hopkinson, Matthew N. (Beilstein Journal of Organic Chemistry, 2024)
2-(Trifluoromethylthio)benzothiazolium triflate (BT-SCF3) was used as deoxyfluorinating reagent for the synthesis of versatile acyl fluorides directly from the corresponding carboxylic acids. These acyl fluorides were reacted with amines in a one-pot protocol to form different amides, including dipeptides, under mild and operationally simple conditions in high yields. Mechanistic studies suggest that BT-SCF3 can generate acyl fluorides from carboxylic acids via two distinct pathways, which allows the deoxyfluorinating reagent to be employed in sub-stoichiometric amounts.
Keywords: acyl fluorides; amides; benzothiazolium salts; carboxylic acids; deoxygenative reactions